Association Between Null Genotypes of Glutathione S-Transferase M1 and T1 and Susceptibility to Systemic Lupus Erythematosus: A Meta-Analysis - Saadat, Mostafa (Scripta Medica, 2024)
Background/Aim: Oxidative stress is involved in the development of systemic lupus erythematosus (SLE). It is well known that activity of the glutathione S-transferase superfamily has a protective effect against oxidative stress. The genes of glutathione S-transferase M1 (GSTM1, a member of mu class) and GSTT1 (a member of theta class) have interesting genetic variation due to deletion of the whole gene and resulting null alleles. Homozygotes for each of these null alleles (null genotypes) have no gene, no protein, and no enzyme activity. Several studies have investigated the association between the GSTT1/GSTM1 polymorphisms and the risk of SLE with inconsistent results. Therefore, the present meta-analysis was performed.  Methods: Eligible publications were identified by searching several databases, 18 case-control studies with 2483 cases and 3643 controls met the inclusion criteria. The raw data of three reports have internal inconsistencies, therefore these studies were excluded from the final analysis.Results: The results showed that the GSTM1 null genotype significantly increased the risk of SLE (OR=1.17, 95% CI: 1.03-1.32, p=0.012) with no evidence of significant heterogeneity (Q=14.53, df=14, p=0.411; I²=3.4%). The GSTT1 null genotype was not associated with the risk of SLE (OR=0.94, 95% CI: 0.80-1.10, p=0.447). There was no evidence of heterogeneity between studies.Conclusion: The present study showed that the null genotype of GSTM1 (and not GSTT1) was weakly associated with the risk of systemic lupus erythematosus.
Keywords: Glutathione S-transferase; GSTT1; GSTM1; Meta-analysis; SLE